Effect of cerebral spinal fluid suppression for diffusional kurtosis imaging. Issue 2 (3rd October 2012) - Yang, Alicia W.; Jensen, Jens H.; Hu, Caixia C.; Tabesh, Ali; Falangola, Maria F.; Helpern, Joseph A.
Abstract Purpose: To evaluate the cerebral spinal fluid (CSF) partial volume effect on diffusional kurtosis imaging (DKI) metrics in white matter and cortical gray matter. Materials and Methods: Four healthy volunteers participated in this study. Standard DKI and fluid‐attenuated inversion recovery (FLAIR) DKI experiments were performed using a twice‐refocused‐spin‐echo diffusion sequence. The conventional diffusion tensor imaging (DTI) metrics of fractional anisotropy (FA), mean, axial, and radial diffusivity (MD, D‖, D⟂) together with DKI metrics of mean, axial, and radial kurtosis (MK, K‖, K⟂), were measured and compared. Single image slices located above the lateral ventricles, with similar anatomical features for each subject, were selected to minimize the effect of CSF from the ventricles. Results: In white matter, differences of less than 10% were observed between diffusion metrics measured with standard DKI and FLAIR‐DKI sequences, suggesting minimal CSF contamination. For gray matter, conventional DTI metrics differed by 19% to 52%, reflecting significant CSF partial volume effects. Kurtosis metrics, however, changed by 11% or less, indicating greater robustness with respect to CSF contamination. Conclusion: Kurtosis metrics are less sensitive to CSF partial voluming in cortical gray matter than conventional diffusion metrics. The kurtosis metrics may then be more specific indicators of changes in tissue microstructure, provided the effect sizes for the changes are comparable. J. Magn. Reson. Imaging 2013;37:365–371. © 2012 Wiley Periodicals, Inc.